Contribution of Kurkuminoid Proteins From White Kunyit Root Extract (Curcuma zedoaria rosc.) ss anti-inflammatory - zubaedah, Siti; Yanti , Hasvika; Widia , Besse; Rompegading, Andi Badli (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research aims to identify curcuminoid compounds from white turmeric (Curcuma zedoaria Rosc.) rhizome extract as anti-inflammatory drugs. White turmeric rhizomes contain curcuminoids which can be used as anti-inflammatory. Curcuminoids are yellow polyphenols, insoluble in water and acidic solvents but soluble in dimethyl sulfoxide, acetone and ethanol. It has various benefits such as lowering blood sugar levels, acting as an antioxidant, and having anti-carcinogenic properties. The identification of curcuminoid compounds in white turmeric as potential anti-inflammatory drugs provides a significant contribution to the development of natural drugs for inflammation-related disorders. The research method used is descriptive through literature research, with a focus on exploring the contents and benefits of white turmeric in traditional medicine. This research provides evidence that supports the efficacy of curcuminoids from white turmeric rhizome extract as an anti-inflammatory agent. However, to validate the effectiveness and safety of using white turmeric as an anti-inflammatory drug in humans, further research is needed including pharmacodynamic studies, pharmacokinetics and clinical trials. Apart from that, purification of curcuminoid compounds and research on interactions with other drugs also need to be carried out to strengthen the scientific basis and develop more effective drug formulations.